Determinants influenceing the mental health of older people (60 years +) in Botswana - Mhaka-Mutepfa, Magen (Magyar Gerontológia, 2022)
Ageing society is a reality for many people in developing countries than in the past. Governments are facing major challenges in safeguarding the mental health of older people and health care systems to deal with this demographic shift. The mental health of older people is an important indicator of the level of their health-related quality of life. The situation of older people in Africa, concerning their mental health and well-being, is a matter of growing attention among researchers and policymakers alike. There is a common perception in connection with the aged population reporting poor mental health status and a greater need for healthcare. However, there is few research on the disparities of older people relating to healthcare in Sub-Saharan Africa, especially in Botswana. There is a tendence of ever-increasing number and population proportions of older people representing both opportunities and challenges. Some of these challenges include the prevention and management of anxiety, depression, and somatization, which are the most common mental disorders in primary health care the world over. Previous research has shown that the three disorders are highly comorbid because of the need for prevention and mitigation of all three.